Air transfer of patients with intra-aortic balloon pump support (Swiss Medical Weekly, 2012)
BACKGROUND AND AIM: Inter-hospital transfers are high-risk operations for critically ill patients dependent on intra-aortic balloon pump (IABP) support. Since September 2008, Swiss Air-Rescue (Rega) has offered such transfers by helicopter. The aim of the present study was to review the first 38 IABP transfers and to promulgate the currently used standard operating procedure (SOP). METHODS: All helicopter transfers of IABP-dependent patients by Swiss Air-Rescue (Rega) between September 2008 and October 2010 were retrospectively analysed. Adverse events (e.g., death), vital parameters and respiratory modus during takeover by the Rega crew and discharge at the receiving hospital, as well as patient demographics, aetiology of heart failure and outcome at the receiving hospital were assessed. RESULTS: A total of 38 IABP transfers occurred, 35 of which were carried out to hospitals within Switzerland. No major adverse events were observed during flight. The mean patient age was 64 ± 11 (mean ± SD) years. The leading cause for IABP support was ischaemic heart failure (32 patients, 84%). The outcome of 35 patients was available: 30 were discharged home or to another institution, and 5 died at the receiving hospital. CONCLUSIONS: Based on these findings, the helicopter transport, the equipment provided, the crew composition and the predefined process offer a safe concept for these complex transfers. The adherence to standard operating procedures is a precondition to achieve excellent quality of care, facilitating and accelerating the hand-over and comprehensive care of such high-risk patients.